A Multi-Classes-Based Algorithm to Provide Flexible QoS Services in B3G Networks - Yue Zhang; Mengqing Jia; Zhiguo Li (2009 5th International Conference on Wireless Communications, Networking and Mobile Computing, 2009)
The provisioning of quality of service (QoS) has become one of the central issues in B3G mobile network design and analysis. The implementation of QoS in the actual network must be established on the end-to-end basis and must provide the service performance levels to obtain the required quality of experience for the users. To address the issue, this paper introduces a multi-classes-based end-to-end quality of service structure to optimize mapping of application level QoS parameters into network-level QoS parameters. Then an algorithm to provide flexible QoS services in B3G networks is provided: Multi-classes-based comparative fairness algorithm (MCCF). In this algorithm, we introduce a weight parameter which could modulate these pure opportunistic resource allocations in order to provide comparative fairness while preserving the system throughput maximization. Simulation results demonstrate the MCCF could get comparative fairness while preserve higher performance simultaneously.